Entanglement in fermionic systems at a quantum phase transition - Johannesson, H.; Larsson, D. (Фізико-технічний інститут низьких температур ім. Б.І. Вєркіна НАН України, 2007)
We consider recent results on the use of the single-site entanglement measure for identifying and characterizing a quantum phase transition in systems of interacting fermions. We discuss the extension of these results to fermionic models where the single-site entanglement may fail to signal a quantum phase transition, with particular attention given to the one-dimensional extendedUV Hubbard model.